Demokrasi lokal di era kenormalan baru: peran media baru dalam pilkada serentak 2020 (Faculty of Communications Science, Dr. Soetomo University, 2023)
The simultaneous local elections in 2020 gave its own color to the implementation of local democracy in Indonesia. The ongoing pandemic situation has forced election organizers to adjust the implementation of the local election to the